Study of Online Content Marketing in the Growth of a Business in the India Market - Sharma, Harish (Digital Repository of Theses, 2024)
The rapid expansion of digital platforms and the evolving landscape of social media have profoundly impacted businesses in India, making online content marketing a crucial component for growth. This study investigates the role of online content marketing in enhancing business growth within the Indian market, emphasizing the challenges posed by shifting social media algorithms and diverse audience preferences (Chaffey & Smith, 2021; Gupta et al., 2023). The research explores how businesses can optimize their content marketing strategies to improve engagement and conversion rates amidst these dynamic conditions. A qualitative research approach was employed, utilizing semi-structured interviews with marketing professionals actively engaged in content marketing across various industries. Participants were selected through purposive sampling, ensuring a diverse representation of experiences and insights related to content marketing in the Indian context (Patel & Kumar, 2022). The thematic analysis of interview data revealed critical factors influencing the effectiveness of content marketing, including audience preferences, cultural nuances, and the quality and relevance of content. The findings underscore the significant impact of social media algorithm changes on the visibility and reach of content, necessitating businesses to frequently adapt their strategies (Smith & Chaffey, 2021). Additionally, the study highlights the importance of leveraging data analytics to understand audience behavior and refine content marketing efforts. The research provides actionable recommendations for businesses to stay competitive, including the need for continuous content optimization and the strategic use of analytics to drive engagement. This study contributes to the existing body of knowledge by offering a nuanced understanding of content marketing in the Indian business environment, framed within the Hierarchy of Effects Model theory (Lavidge & Steiner, 1961). The insights gained can guide marketers in developing more effective content strategies that align with the rapidly changing digital landscape in India. Future research should explore the long-term effects of content marketing strategies on business growth, the role of emerging technologies in content creation, and the ethical considerations in digital marketing practices.